The Functional Reception of Qur'anic Calligraphy at the Grand Mosque of Nurul Islam, Palangka Raya - Hamidinnor, Hamidinnor; Tahe, Nur Amimi; Munirah, Munirah; Supriadi, Akhmad; Malisi, M. Ali Sibram (Al-Qudwah, 2024)
Nurul Islam Grand Mosque, recognized as the first and oldest grand mosque in Palangka Raya, Central Kalimantan, is distinguished primarily by its extensive Qur’anic calligraphy that adorns nearly the entire interior, including the walls and ceiling. This study investigates the functional reception of the calligraphy, focusing on the selection of specific Qur’anic verses and the rationale behind their inclusion. Employing a qualitative methodology with a descriptive-analytical approach, the research is grounded in Qur’anic reception theory, particularly the concept of functional reception. Data were collected through fieldwork involving observation, interviews, and documentation. The findings reveal that the verses featured in the mosque are those frequently recited and memorized by Muslims in daily practice, such as Surah Yāsīn, Al-Wāqi‘ah, and Al-Mulk. The functional reception is manifested in the curatorial decision to present these verses as calligraphy, thereby enabling visitors to engage with the surahs or verses without the need to consult a mushaf, in addition to serving an ornamental purpose. Furthermore, the calligraphy contributes to the mosque’s unique aesthetic identity, distinguishing it from other mosques. However, issues related to the legibility of certain calligraphic elements have elicited criticism, suggesting that the mosque’s administration should address these concerns appropriately.Abstrak: Masjid Raya Nurul Islam merupakan masjid raya pertama sekaligus tertua di Palangka Raya, Kalimantan Tengah. Keunikan utamanya terletak pada hampir seluruh bagian interior yang dihiasi kaligrafi Al-Qur’an, mulai dari dinding hingga plafon. Penelitian ini bertujuan untuk menelaah bagaimana resepsi fungsional terhadap kaligrafi tersebut, ayat-ayat apa yang dipilih, serta alasan pemilihan ayat. Metode yang digunakan ialah kualitatif dengan pendekatan deskriptif-analitis, berlandaskan teori resepsi Al-Qur’an, khususnya resepsi fungsional. Riset ini bersifat lapangan dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukan bahwa ayat yang ditampilkan pada Masjid Raya Nurul Islam adalah ayat-ayat yang umum dibaca dan dihapal oleh umat Islam sehari-hari seperti QS. Yasin, QS. al-Waqi’ah, QS. al-Mulk dan lain-lain. Adapun bentuk resepsi fungsional kaligrafi Al-Qur’an terlihat pada pemilihan ayat yang dituliskan menjadi kaligrafi di Masjid Raya Nurul Islam, di mana ayat-ayat yang dituliskan selain dijadikan hiasan juga memudahkan pengunjung yang ingin membaca surah-surah atau ayat-ayat Al-Qur’an tanpa harus mencari di dalam Al-Qur’an. Selain itu, dengan kaligrafi tersebut Masjid Raya Nurul Islam memilki daya tarik tersendiri yang membedakannya dengan masjid lain. Di sisi lain, keberadaan tulisan yang kurang terbaca memunculkan kritik yang patut dicermati oleh pengurus masjid.